2022
DOI: 10.1159/000524623
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Assessing the Underrepresentation of Cancer Patients in COVID-19 Trials

Abstract: Background - The new severe acute respiratory syndrome coronavirus 2 have emerged as a global pandemic that threatens thousands around the world. Observational cohort studies have demonstrated that cancer patients have inferior outcomes due to underlying malignancy, treatment-related immunosuppression, or increased comorbidities. We aimed to examine the representation of cancer patients (hematological malignancies and solid tumors) in COVID-19 therapeutic and prophylactic interventional trials. Methods- In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Buchrits et al [4] performed a systematic review, including all interventional randomized controlled trials evaluating currently recommended drugs to treat CO-VID-19. This systematic review included 22 publications, only two explicitly reported inclusion of cancer patients, and none reported outcomes specifically for this subgroup.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Buchrits et al [4] performed a systematic review, including all interventional randomized controlled trials evaluating currently recommended drugs to treat CO-VID-19. This systematic review included 22 publications, only two explicitly reported inclusion of cancer patients, and none reported outcomes specifically for this subgroup.…”
mentioning
confidence: 99%
“…This systematic review included 22 publications, only two explicitly reported inclusion of cancer patients, and none reported outcomes specifically for this subgroup. Hence, physicians treating COVID-19 patients with hematological malignancy should be aware of the limited generalizability of data on therapeutic options for this population [4].…”
mentioning
confidence: 99%